VISUALISASI PROSES DALAM GENERATOR LISTRIK DENGAN PENDEKATAN KOGNITIF-BEHAVIORISTIK UNTUK PEMBELAJARAN SISWA SMK - Agus Setyawan; Edi Noersasongko; Stefanus Santosa (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2019)
Power generation is one of the learning materials in Competence Expertise Electricity, methods of tutorials, lectures and question and answer and practices originating in the textbook or modules used in learning. Obstacle field practice that is in addition to equipment is limited, some generators have been damaged either due to aging or installation errors of the students on practice time. It is also to know more clearly about the working principle of electric generators in this case is the magnetic field and rotor rotation that can generate electricity learners understand the difficulty because the occurrence is in the generator with a closed circuit. In reality the practice field to meet the ideal lesson about electrical generators required is expensive and the more generators are turned on at the same time will generate noise that can interfere with other learners. Appropriate learning method is to use the visualization method in this case is by displaying the symbols or tools that illustrate the process of installation of electricity generators and the actual electricity generation process, including the parts of the generator, such as: rotor, stator, the anchor and the commutator. Research done by making the model visualization in the form of interactive multimedia animations and equipped with control equipment that can be operated by users, so users can choose what you want to proceed. From the data showed that the media system in the form of generator power this gives a positive contribution to the understanding of student learning.